Tópicos de defeitos em teoria clássica de campos - Bezerra, Isaiane Rocha (2023)
In this work, we deal with topological and non-topological defects in classical field theory. We study the topological structures, referred to as kinks, and the non-topological structures, referred to as lumps, that arise in models of one and two real scalar fields in (1, 1) spacetime dimensions. We also deal with deformed localized structures. We investigate and characterize the potential models in terms of equations of motion, energies, and stabilities of static solutions. Finally, we construct, investigate and present explicit defect solutions that arise from the coupling of two fields that support distinct types of defects.